KrafT Bildungsdokumentation: Kind- und ressourcenorientierte, analysebasierte, fortschrittsorientierte Bildungsbegleitung im Team planen, dokumentieren und reflektieren. Herausgegeben von: Büker, Petra; Ogrodowski, Jana, und Antenbrink, Teresa - Herding, Jana

Corona und Krise. Perspektiven erziehungswissenschaftlicher Frauen- und Geschlechterforschung - Mattei, Annalisa; Eremin, Oxana (Bericht zur Jahrestagung der Sektion Frauen- und Geschlechterforschung in der Erziehungswissenschaft in der Deutschen Gesellschaft für Erziehungswissenschaft)

Rezension zu: Nef, Susanne: Ringen um Bedeutung. Die Deutung häuslicher Gewalt als sozialer Prozess, Basel 2020, in: Fegter, Susann / Langer, Antje / Thon, Christine (Hgg.): Diskursanalytische Geschlechterforschung in der Erziehungswissenschaft - Mattei, Annalisa (Jahrbuch Erziehungswissenschaftliche Geschlechterforschung 17, Opladen / Berlin / Toronto)

Jahrestagung „Corona und Krise – Perspektiven erziehungswissenschaftlicher Frauen- und Geschlechterforschung“ Erziehungswissenschaft Heft 63, Jg. 32|2021 - Mattei, Annalisa; Eremin, Oxana

Entwicklungschance oder Warteschleife? Berufsorientierung und Berufswahl in der Berufsfachschule - Schemmer, Susanne Jutta; Heisler, Dietmar; Rink, Julia (Entwicklungen und Perspektiven in der Berufsorientierung. Stand und Herausforderungen. Online: (06.12.2021))

Carbon Dating of Seven Parchment Qurʾān Manuscripts and One Syriac Bible of the National Museum of Iran - Aghaei Abrandabadi, Seyed Ali; Marx, Michael (Journal of Iranian National Museum, 2)

David und Salomon im Koran: ein Komparativ-theologischer Ansatz - Saad, Nadia (Erlanger Jahrbuch für Interreligiöse Diskurse. Methoden der Darstellung und Analyse interreligiöser Diskurse)

I-AID: Identifying Actionable Information From Disaster-Related Tweets - Zahera, H.M.A; Jalota, Rricha; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science

ASSET: A Semi-supervised Approach for Entity Typing in Knowledge Graphs - Zahera, H.M.A; Heindorf, Stefan; Ngomo, Axel-Cyrille Ngonga (Proceedings of the 11th on Knowledge Capture Conference)

Essays on Modeling Languages and Software Tools for Business Model Innovation: Theory and Empirical Evidence - Szopinski, Daniel

Decomposition-Guided Reductions for Argumentation and Treewidth - Fichte, Johannes; Hecher, Markus; Mahmood, Yasir; Meier, Arne (Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence)
Argumentation is a widely applied framework for modeling and evaluating arguments and its reasoning with various applications. Popular frameworks are abstract argumentation (Dung’s framework) or logic-based argumentation (Besnard-Hunter’s framework). Their computational complexity has been studied quite in-depth. Incorporating treewidth into the complexity analysis is particularly interesting, as solvers oftentimes employ SAT-based solvers, which can solve instances of low treewidth fast. In this paper, we address whether one can design reductions from argumentation problems to SAT-problems while linearly preserving the treewidth, which results in decomposition-guided (DG) reductions. It turns out that the linear treewidth overhead caused by our DG reductions, cannot be significantly improved under reasonable assumptions. Finally, we consider logic-based argumentation and establish new upper bounds using DG reductions and lower bounds.

Parameterised complexity of model checking and satisfiability in propositional dependence logic - Mahmood, Yasir; Meier, Arne (Annals of Mathematics and Artificial Intelligence)
Abstract Dependence Logic was introduced by Jouko Väänänen in 2007. We study a propositional variant of this logic (PDL) and investigate a variety of parameterisations with respect to central decision problems. The model checking problem (MC) of PDL is NP -complete (Ebbing and Lohmann, SOFSEM 2012). The subject of this research is to identify a list of parameterisations (formula-size, formula-depth, treewidth, team-size, number of variables) under which MC becomes fixed-parameter tractable. Furthermore, we show that the number of disjunctions or the arity of dependence atoms (dep-arity) as a parameter both yield a paraNP-completeness result. Then, we consider the satisfiability problem (SAT) which classically is known to be NP -complete as well (Lohmann and Vollmer, Studia Logica 2013). There we are presenting a different picture: under team-size, or dep-arity SAT is paraNP -complete whereas under all other mentioned parameters the problem is FPT . Finally, we introduce a variant of the satisfiability problem, asking for a team of a given size, and show for this problem an almost complete picture.
Keywords: Applied Mathematics; Artificial Intelligence

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Accounting for Heuristics in Reputation Systems: An Interdisciplinary Approach on Aggregation Processes - van Straaten, Dirk; Melnikov, Vitalik; Hüllermeier, Eyke; Mir Djawadi, Behnud; Fahr, René
Aggregation metrics in reputation systems are important for overcoming information overload. When using these metrics, technical aggregation functions such as the arithmetic mean are implemented to measure the valence of product ratings. However, it is unclear whether the implemented aggregation functions match the inherent aggregation patterns of customers. In our experiment, we elicit customers' aggregation heuristics and contrast these with reference functions. Our findings indicate that, overall, the arithmetic mean performs best in comparison with other aggregation functions. However, our analysis on an individual level reveals heterogeneous aggregation patterns. Major clusters exhibit a binary bias (i.e., an over-weighting of moderate ratings and under-weighting of extreme ratings) in combination with the arithmetic mean. Minor clusters focus on 1-star ratings or negative (i.e., 1-star and 2-star) ratings. Thereby, inherent aggregation patterns are neither affected by variation of provided information nor by individual characteristics such as experience, risk attitudes, or demographics.

Incentive Schemes in Customer Rating Systems - Comparing the Effects of Unconditional and Conditional Rebates on Intrinsic Motivation - van Straaten, Dirk

Fighting Fire with Fire - Overcoming Ambiguity Aversion by Introducing more Ambiguity - van Straaten, Dirk; Fahr, René

Political Speaker Transfer: Learning to Generate Text in the Styles of Barack Obama and Donald Trump - Bülling, Jonas

Computational Text Professionalization using Neural Sequence-to-Sequence Models - Mishra, Avishek

ReconOS64: High-Performance Embedded Computing for Industrial Analytics on a Reconfigurable System-on-Chip - Clausing, Lennart (Proceedings of the 11th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Relaxed parameter conditions for chemotactic collapse in logistic-type parabolic–elliptic Keller–Segel systems - Black, Tobias; Fuest, Mario; Lankeit, Johannes (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Prescribed signal concentration on the boundary: Weak solvability in a chemotaxis-Stokes system with proliferation - Black, Tobias; Wu, Chunyan (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

A composite consisting of intermetallic Ni3Fe and nitrogen-doped carbon for electrocatalytic water oxidation: The effect of increased pyridinic nitrogen dopant - Liu, Dan; Zhai, Haichao; Hu, Jie; Pan, Ying; Xu, Gengsheng; Zhu, Chuhong; Yuan, Yupeng (Ceramics International)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Process Chemistry and Technology; Ceramics and Composites; Electronic; Optical and Magnetic Materials

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Carbon-Based Metal-Free Electrocatalysts: Past, Present, and Future - Zhai, Qingfeng; Pan, Ying; Dai, Liming (Accounts of Materials Research)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Chemical Engineering (miscellaneous)

Strain‐Engineered Nano‐Ferroelectrics for High‐Efficiency Piezocatalytic Overall Water Splitting - Su, Ran; Wang, Zhipeng; Zhu, Lina; Pan, Ying; Zhang, Dawei; Wen, Hui; Luo, Zheng‐Dong; Li, Linglong; Li, Fa‐tang; Wu, Ming; He, Liqiang; Sharma, Pankaj; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A universal electrochemical activation enabling lattice oxygen activation in nickel-based catalyst for efficient water oxidation - Hu, Jie; Jiang, Daochuan; Weng, Zhaoyue; Pan, Ying; Li, Zhongjun; Du, Haiwei; Yuan, Yupeng (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Cascaded dual-loop organic Rankine cycle with alkanes and low global warming potential refrigerants as working fluids - Abbas, Wameedh Khider Abbas; Vrabec, Jadran (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Der Einfluss der Besteuerung auf Managementanreize und die Nutzung von Bonusbanken - Dyck, Daniel (Junior Management Science)

Editorial: Schmalenbach IMPULSE: Will etwas in Bewegung setzen - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

CoViD-19 als Katalysator für die digitale Professionalisierung angehender Lehrpersonen? - Schwabl, Franziska; Vogelsang, Christoph (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Die CoViD-19-Pandemie ab Frühjahr 2020 und die pandemiebedingten Kontaktbeschränkungen hatten erhebliche Auswirkungen auf die studienbegleitenden Praxisphasen im Lehramtsstudium. Studierende, die ihr Praxissemester im Sommersemester 2020 absolvierten, waren in der Folge erheblich von Einschränkungen sowohl während der universitären Begleitveranstaltungen als auch in den Praxisschulen betroffen. Durch die überwiegende Umstellung von Präsenzformaten zu digitalem Lehren und Lernen auf Distanz ist die Annahme naheliegend, dass Studierende vermehrt die Möglichkeit hatten, Erfahrungen mit digitalen Lernformaten zu machen. Anhand einer Sekundäranalyse der Befragung einer Kohorte von Praxissemesterstudierenden der Universität Paderborn (N=362) kann allerdings gezeigt werden, dass der erwartete Möglichkeitsraum für eine digitale Professionalisierung keineswegs ausgeschöpft bzw. überhaupt genutzt wurde. Vielmehr zeigte sich, dass angehende Lehrpersonen digitale Medien vor allem dann in den eigenen Unterricht einbetten, wenn diese in der mentoriellen Begleitung thematisiert wurde oder während Hospitationen beobachtet werden konnte. Zudem deuten die Analysen an, dass ungünstige Professionalisierungsbedingungen an den Praxisschulen nur bedingt durch die universitären Anteile der Praxisphasen aufgefangen werden konnten. Für die Gestaltung der universitären Lehrpersonenausbildung ergibt sich daher u. a. die Notwendigkeit einer intensiveren Kooperation zwischen den verschiedenen Akteuren der drei Phasen der Lehrpersonenbildung.

Selbstreguliertes Lernen im berufsschulischen Übergangssystem - Daniel-Söltenfuß, Desiree; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Selbstreguliertes Lernen fördern - Lernen auf Distanz ermöglichen - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

Effectiveness of health-oriented leadership interventions for improving health and wellbeing of employees: a systematic review - Dannheim, Indra; Ludwig-Walz, Helena; Buyken, Anette; Grimm, Valerie; Kroke, Anja (Journal of Public Health)
Abstract Aim To identify and summarize the evidence for the effect of health-oriented leadership interventions on health and well-being outcomes at the employee level following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Moher et al. 2009). Subject and Methods A systematic search of relevant studies was conducted in multiple databases. Randomized controlled trials (RCTs), cluster-randomized controlled trials (cRCTs) and controlled before–after studies (CBAs) were included based on the following criteria: interventions that addressed supervisors, to raise awareness for the importance of health issues, teach mindfulness practices for conscious awareness, reduce stress and promote resources at the level of individual behavior, and evaluated the effect on at least one outcome of psychomental stress, absenteeism and well-being on the employee level. Results Of 6126 publications retrieved, ten studies were identified for analysis. Significant effects of leadership training were reported on exhaustion tendency, self-reported sickness absence, work-related sickness absence and job satisfaction in studies comparing health-oriented training programs to no intervention. Studies comparing health-oriented leadership training to other training did not report significant effects. Risk of bias was judged to be high in seven studies and unclear in three studies. Conclusion Evidence for the effectiveness of health-oriented leadership interventions on employees’ stress, absenteeism or well-being is judged to be low, clearly indicating the need for more and higher-quality research.
Keywords: Public Health; Environmental and Occupational Health

Zur Einführung in Kapitel 10 und 11 - Grimminger-Seidensticker, Elke; Brandl-Bredenbeck, Hans Peter; Gerlach, Erin; Krieger, Claus (Sportpädagogik. Eine Grundlegend)

Forschungsmethodische Zugänge - Grimminger-Seidensticker, Elke; Krieger, Claus (Sportpädagogik. Eine Grundlegung)

Des arbitrages éthiques face aux injonctions à la pratique physique dans les programmes de promotion de la santé : le cas des familles populaires en Europe - Grimminger-Seidensticker, Elke; Vieille Marchiset, G.; Knobé, S.; Aceti, M. (SociologieS.)

Der historische Muhammad in der islamischen Theologie. Zur Kriterienfrage in der Leben-Muhammad-Forschung - Ghaffar, Zishan

Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Zum Einfluss der Erstsprache auf den Gebrauch von Präpositionen. Eine kontrastive Analyse im Lernerkorpus MERLIN. - Weber, Tassja (Deutsch im Vergleich. Theorie, Praxis, Didaktik.)
Die Verknüpfung kontrastiver Linguistik und Didaktik ist in der linguistischen Forschung von besonderer Bedeutung und steht im Mittelpunkt dieses Bandes. Mit dem Band werden einige der Themen aus der internationalen Tagung Kontrastive Linguistik vertieft, die 2018 an der Universität Mailand stattfand. Die zwölf Beiträge fokussieren sowohl theoretisch als auch praxisorientiert wichtige Merkmale des Deutschen, das mit anderen Sprachen (wie Italienisch, Englisch und Spanisch) durch vielfältige Methoden (u.a. Korpuslinguistik und Textlinguistik) verglichen wird. Dabei präsentieren sie neue Perspektiven für den didaktischen Bereich und tragen somit zur Diskussion der Potenziale der kontrastiven Analysen in den Bereichen der Mehrsprachigkeit, der Syntax und der Phonetik/Phonologie bei.

Eigenvalue spectra of QCD and the fate of UA(1) breaking towards the chiral limit - Kaczmarek, Olaf; Mazur, Lukas; Sharma, Sayantan (Physical Review D)

Heavy quark momentum diffusion from the lattice using gradient flow - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, H.-T. (Physical Review D)

Sphaleron rate from Euclidean lattice correlators: An exploration - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, H.-T. (Physical Review D)

High-Performance Spectral Element Methods on Field-Programmable Gate Arrays : Implementation, Evaluation, and Future Projection - Karp, Martin; Podobas, Artur; Jansson, Niclas; Kenter, Tobias; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (2021 IEEE International Parallel and Distributed Processing Symposium (IPDPS))

The Form of Truth. Hegel’s Philosophical Logic. - Ficara, Elena

Quality Criteria for Conceptual Technology Integration Models in Education: Bridging Research and Practice. Educational Technology Research and Development - Tondeur, J; Petko, D; Christensen, R; Starkey, L; Drossel, Kerstin; Eichhorn, K; Schmidt-Crawford, D; Knezek, D (Educational Technology Research and Development)

Reconfigurable and Real-Time Nyquist OTDM Demultiplexing in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Electrical Engineering and Systems Science)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain demultiplexing of coherent multilevel Nyquist signals in silicon photonics. No external pulse source is needed and frequencytime coherence is used to sample the incoming Nyquist OTDM signal with orthogonal sinc-shaped Nyquist pulse sequences using Mach-Zehnder modulators. All the parameters such as bandwidth and channel selection are completely tunable in the electrical domain. The feasibility of this scheme is demonstrated through a demultiplexing experiment over the entire C-band (1530 nm - 1550 nm), employing 24 Gbaud Nyquist QAM signals due to experimental constraints on the transmitter side. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can demultiplex Nyquist pulses of 90 GHz optical bandwidth suggesting a possibility to reach symbol rates up to 90 GBd in an integrated Nyquist transceiver.

Unterstützung des Modellierungsprozesses durch Analogiebildung im Sachunterricht - Elsner, Julia; Tenberge, Claudia; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)

LIMES - A Framework for Link Discovery on the Semantic Web - Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Georgala, Kleanthi; Hassan, Mofeed; Dreßler, Kevin; Lyko, Klaus; Obraczka, Daniel; Soru, Tommaso (KI - Künstliche Intelligenz, German Journal of Artificial Intelligence - Organ des Fachbereichs "Künstliche Intelligenz" der Gesellschaft für Informatik e.V.)
The Linked Data paradigm builds upon the backbone of distributed knowledge bases connected by typed links. The mere volume of current knowledge bases as well as their sheer number pose two major challenges when aiming to support the computation of links across and within them. The first is that tools for link discovery have to be time-efficient when they compute links. Secondly, these tools have to produce links of high quality to serve the applications built upon Linked Data well. Solutions to the second problem build upon efficient computational approaches developed to solve the first and combine these with dedicated machine learning techniques. The current version of the LIMES framework is the product of seven years of research on these two challenges. A series of machine learning techniques and efficient computation approaches were developed and integrated into this framework to address the link discovery problem. The framework combines these diverse algorithms within a generic and extensible architecture. In this article, we give an overview of version 1.7.4 of the open-source release of the framework. In particular, we focus on an overview of the architecture of the framework, an intuition of its inner workings and a brief overview of the approaches it contains. Some descriptions of the applications within which the framework was used complete the paper. Our framework is open-source and available under a GNU license at https: //github.com/dice-group/LIMES together with a user manual and a developer manual.
Keywords: 2021 dice simba sherif limes ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limbo opal georgala kevin slipo sage